2018
DOI: 10.3390/ijms20010033
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Tools to Monitor the Changes in Translation Efficiency of Plant mRNA on a Genome-Wide Scale: Advantages, Limitations, and Solutions

Abstract: The control of translation in the course of gene expression regulation plays a crucial role in plants’ cellular events and, particularly, in responses to environmental factors. The paradox of the great variance between levels of mRNAs and their protein products in eukaryotic cells, including plants, requires thorough investigation of the regulatory mechanisms of translation. A wide and amazingly complex network of mechanisms decoding the plant genome into proteome challenges researchers to design new methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 71 publications
(141 reference statements)
0
27
0
Order By: Relevance
“…Several approaches have been designed and are used for delivering the gene constructs for transient expression: transfection of protoplasts using polyethylene glycol (PEG) or electroporation [ 20 ], biolistics [ 21 ], and agroinfiltration [ 7 ]. Numerous studies have convincingly demonstrated their efficacy for characterization of gene functions, including assessment of subcellular localization of protein products of the target genes, study of the signal transduction pathways, and protein–protein interaction [ 22 , 23 ], as well as for clarifying the functional properties of regulatory sequences in plants and so on [ 1 , 24 , 25 ]. Each system of transient gene expression in plants as well as the approaches to the delivery of gene constructs along with its specific advantages has its own limitations and bottlenecks depending on the goal of a particular research.…”
Section: Transient Expression Of Heterologous Genes: Plant Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several approaches have been designed and are used for delivering the gene constructs for transient expression: transfection of protoplasts using polyethylene glycol (PEG) or electroporation [ 20 ], biolistics [ 21 ], and agroinfiltration [ 7 ]. Numerous studies have convincingly demonstrated their efficacy for characterization of gene functions, including assessment of subcellular localization of protein products of the target genes, study of the signal transduction pathways, and protein–protein interaction [ 22 , 23 ], as well as for clarifying the functional properties of regulatory sequences in plants and so on [ 1 , 24 , 25 ]. Each system of transient gene expression in plants as well as the approaches to the delivery of gene constructs along with its specific advantages has its own limitations and bottlenecks depending on the goal of a particular research.…”
Section: Transient Expression Of Heterologous Genes: Plant Systemsmentioning
confidence: 99%
“…The first steps in the study of this problem were made owing to a deep insight into the mechanisms of transcription control as the first stage of gene expression and the easiest one for experiments in the methodical aspect. High-throughput technologies for transcriptome analysis, such as RNA-Seq and microarrays, have considerably clarified the key mechanisms underlying the regulation of gene transcription, expanded our knowledge about the transcriptional control of gene(s), and provided convincing experimental data demonstrating dynamic changes in transcriptomes of different plant species during their growth, development, and response to manifold environmental factors [ 1 , 2 ]. A large volume of data on gene expression obtained in comparative omic studies and, as a rule, meticulously processed with the help of available bioinformatics tools has made it possible to reveal the common transcriptome networks controlling a certain function and to predict the role of particular genes in cell processes [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review interrelates recent discoveries on translational gene regulation of cytosolic mRNAs in seed plants, building on previous excellent reviews on the same topic (Browning & Bailey-Serres, 2015;Goldenkova-Pavlova et al, 2018;Mazzoni-Putman & Stepanova, 2018;Merchante, Stepanova, & Alonso, 2017). We begin at the level of cellular "systems" physiology emphasizing, in order, metabolic control of global protein synthesis, genome-wide studies of translational control in response to environmental perturbations, and the role of ribonucleoprotein granules.…”
Section: Introductionmentioning
confidence: 95%